Digital Marketing for Goals Sustainability - Supriyati, S; Budi, G S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The objective of this study is to know how big the influence of digital marketing in marketing communication strategy. Digital marketing is one of the tool to promote a product through media. Beside that, digital marketing can also facilitate the producer and the consumer into doing the buy and sell process. The method used in this study is descriptive method with qualitative approach. This study is caused by the rapid growth of technology in Indonesia, which caused digital marketing involved in marketing process. The result of this study shows that there is an impact from digital marketing in a marketing process. In conclusion, digital marketing is one of the main needs in marketing process that cannot be left out. With the rapid growth of technology, digital marketing is more affordable than any other methods. Besides, with the existence of digital marketing, it also facilitates the producer and consumer.